Approach to the Patient with Accidentally Swallowing a Needle - Hotmen Sijabat; Budiman Sudjatmika; Marcellus Simadibrata (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2008)
People are capable of ingesting, inserting, or injecting themselves or others with all manner of foreign objects. Ingested or inserted foreign bodies may cause bowel obstruction or perforation; which lead to severe hemorrhage, abscess formation, or septicemia; or distant embolization. Fortunately, once a foreign body has reached the stomach, it has an 80-90% chance of passage. All sharp foreign bodies should be removed before they pass from the stomach because 15-35% of these will cause intestinal perforation, usually in the area of the ileocecal valve. The abdominal radiograph should be made and repeated to confirm the location of foreign bodies. If a sharp foreign body does not progress for three consecutive days, surgical intervention should be considered and, if the patient becomes symptomatic, surgical intervention will be necessary. In this case, the patient had accidentally swallowed needle 2 days prior to admission, with no complaint any symptoms of abdominal discomfort, and no bloody stools. Observation is the treatment of choice for this case, since needle had passed stomach and reached colon, and it is hoped that the needle pass through without any complication. Keywords: sharp foreign bodies, needle, swallowing